Scaling up interpersonal psychotherapy training: A pilot randomized controlled trial of digital asynchronous self-directed vs. synchronous group workshop training - Paula Ravitz; Natalie Heeney; Andrea Lawson; Edward McAnanama; Clare Pain; Alex Kiss; Priya Watson; Jan Malat; Sophie Grigoriadis; Simone Vigod; Daisy R. Singla (Journal of Affective Disorders Reports)
Background: Interpersonal Psychotherapy (IPT) is an effective depression treatment but limited numbers of trained providers result in less access than patients need. Asynchronous self-directed digital training may reduce this gap. Methods: We developed digital IPT training and evaluated it in a pilot parallel randomized controlled trial. Psychiatry residents (N=25) in Toronto, Canada, were randomly assigned, 1:1, to an asynchronous self-directed digital course (intervention; n=13) or synchronous group training-as-usual workshop (control; n=12) and then delivered ∼12 clinically-supervised individual IPT sessions to depressed patients (N=26; 10≥PHQ9<20). The primary objective was to examine intervention feasibility and acceptability (retention, facilitators, barriers). We also examined resident competence (IPT knowledge, confidence, clinical skills, therapeutic alliances) and patient depressive outcomes (PHQ9). Results: Resident retention in intervention (10/13; 76.9%) vs control (11/12; 91.7%) groups did not differ (p=.59). Qualitative semi-structured interviews with intervention residents (n=10) revealed that IPT's relational focus, video-recorded expert demonstrations (9/10; 90%), and case-based digital curriculum's user-friendliness (7/10; 70%) were facilitators. Half missed peer interactions in group workshops and found some interactive course elements disrupted learning. Both groups’ competence improved over time (F≥25.7, p≤.0001), with no significant between-arm differences in knowledge, confidence, skills, or therapeutic alliances (F≤1.07, p≥.31). Intervention and control patient groups improved from baseline (PHQ9=14.6 vs. 13.2; F=24.4, p=.0001), with no significant between-arm post-treatment depressive symptom differences (PHQ9=7.63 vs. 7.60, t=-0.01, p=.99). Limitations: Small sample and provider type (psychiatry resident) limit generalizability. Conclusion: Digital asynchronous self-directed IPT training is feasible and acceptable, with preliminary evidence of efficacy for trainee competence and patient outcomes.